AKTUALISASI LANGIT BARU DAN BUMI BARU MENURUT WAHYU 21:1-4 DALAM PENDIDIKAN PERDAMAIAN - Marlyn Kayadoe (Diegesis : Jurnal Teologi, 2023)
Peace is not created by itself but strived for, built, and created by humans. This is clearly illustrated in the concept of a new heaven and a new earth according to Revelation 21:1-4. Revelation 21:1-4 provides a new picture of life, new relationships, and new conditions where humans live side by side in peace without fear, intimidation, oppression, violence, chaos, and conflict. It takes a consensus with all parties to realize these conditions. This research explores the concept of a new heaven, a new earth, and its implications for reconciliation. The research method used is qualitative with a hermeneutic approach. The study shows that actualizing the concept of a new heaven and a new earth in peace education is an essential part of efforts to create peace on earth. A deeper understanding of this concept will provide a new perspective on peace and its implementation in peace education.